Approaching a Nearly Zero Energy Building Integrated with PCM by Optimization of Energy Sources - Ali Sulaiman Alsagri (Buildings)
In recent years, population growth, the enhancement of carbon emissions generation, and higher energy consumption have caused the movement to nearly zero-energy buildings. Additionally, the various strategies, phase change materials (PCMs) are suitable for reducing the energy consumption of a building. The focus of this study is to investigate the results of three scenarios that explore all the effective parameters for selecting a suitable Phase Change Material (PCM) for hot climate conditions in Saudi Arabia. The first scenario worked on choosing the best phase change material based on the climatic conditions and the selected area. To complete the optimization, the best thickness and placement of the two-layer phase change material were investigated in the second and third scenarios. The results indicated that optimized building using PCM 29 with 50 mm thickness reduced the energy consumption and carbon dioxide production by 20.72% and 21.05%, respectively. Furthermore, the outcomes of the study on two-layer phase change materials with different arrangements illustrated that the most proper location of PCMs caused 255.38 MWh of electricity consumption and 155.71 × 103 kg of carbon dioxide production. Finally, as a novel integration, the results of using one-layer and two-layer PCM were added to the HOMER software to find the optimal hybrid energy systems. The findings showed that by integrating photovoltaic panels, diesel generation, batteries, and the grid, the cost of energy reached USD 0.162. Additionally, the grid purchase by using one-layer and two-layer phase change material was decreased by 21.2% and 24.3% compared to the base case.